FORSPA initiative for rehabilitation of tropical forests in Asia-Pacific region - Appanah, S.; Nair, C.T.S. (Center for International Forestry Research, 2001)
Tropical forests of the Asia-Pacific region are the most heavily threatened from high population density and rapid economic growth. Extensive forest areas have become degraded as a result of over-exploitation and poor management. Unless these degraded forests are rehabilitated, they will come under pressure from other land uses. Recognising this, the Forest Research Support Programme for Asia and the Pacific (FORSPSA) of FAO initiated a Rehabilitation Programme and has started to set up a series of model plots of about 100 ha in each of the eco-climatic regions of Asia and the Pacific. Unproductive second growth forest areas will be rehabilitated using indigenous species of commercial value and techniques that are most familiar locally and well-proven. The plots will be model areas for research and training extend the methods to other parts of the region with similar ecological conditions. These plots, which are accessible to international scientists, will be maintained for long enough to achieve and extend results. To further enhance the rehabilitation work, the group of scientists and forest managers will be soon linked through the Asia Pacific Forest Rehabilitation Network (APFReN). This will link together scientists and managers engaged in rehabilitation work to share experiences and solve problems. The Rehabilitation Programme will include training courses, workshops and publication of literature on forest rehabilitation issues.